2000
DOI: 10.1016/s0006-3495(00)76382-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Morphodynamics of Endothelial Cells within Confluent Cultures in Response to Fluid Shear Stress

Abstract: To evaluate shear stress-induced effects on cultured cells we have extended the mechanical setup of a multichannel in vitro rheological system and developed software allowing entire processing control and image data analysis. The values of cell motility, degree of orientation (alignment), and cell elongation were correlated as a function of time (morphodynamics). Collective and individual endothelial cells within confluent cultures displayed a shear stress-dependent characteristic phase behavior of the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 71 publications
(85 reference statements)
5
61
0
Order By: Relevance
“…Detailed quantitative analyses of shear stress-induced morphologic changes as a function of time (morphodynamics) showed that endothelial cells within confluent cultures pass through different phases (Dieterich et al, 2000). Phase I corresponds to resting conditions or very low shear stress values, and is characterized by random cell orientation, polygonal cell shape, and a moderate mean migration (locomotion) of the cells (ie, cell centers) that is associated with extended zigzag movements (fluctuations) around the mean locomotion trajectories.…”
Section: Institut Für Biochemie (Js H-jg) Wwu-münster Münster Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed quantitative analyses of shear stress-induced morphologic changes as a function of time (morphodynamics) showed that endothelial cells within confluent cultures pass through different phases (Dieterich et al, 2000). Phase I corresponds to resting conditions or very low shear stress values, and is characterized by random cell orientation, polygonal cell shape, and a moderate mean migration (locomotion) of the cells (ie, cell centers) that is associated with extended zigzag movements (fluctuations) around the mean locomotion trajectories.…”
Section: Institut Für Biochemie (Js H-jg) Wwu-münster Münster Recmentioning
confidence: 99%
“…Recently we described a novel rheological setup and novel software, also used in the present study, that can be used to analyze morphodynamic parameters (Dieterich et al, 2000). Morphodynamics are defined as changes in cell motility, cell orientation, and cell elongation, as functions of time.…”
Section: Correlation Of Shear Stress-induced Changes In Ter With Morpmentioning
confidence: 99%
“…The so-called morphodynamics approach to quantitatively analyzing shear stressinduced morphological changes in ECs with respect to time that Dieterich et al (2000) employed was able to elucidate the different phases that ECs go through in response to the onset and continuation of shear stress exposure. Phase I is characterized by random cell orientation and polygonal cell shape during resting conditions or very low shear stress.…”
Section: Effect Of Shear Stressmentioning
confidence: 99%
“…In addition to fluorescent detection, cells can be monitored in migration assays by time-lapse video microscopy (Young and Simmons, 2010) or by using the morphodynamics approach of Dieterich et al (2000). Possible concerns involved with using fluid flow to produce chemical gradients (as is often done by mixing laminar fluid streams in microchannels) for chemotactic studies is that shear stress effects may obscure or confound results that are intended to measure cell migration towards a chemical source.…”
Section: Migration Assaymentioning
confidence: 99%
“…However, to understand pathogenic and physiological processes taking place during atherosclerotic developments in more detail we suggest a fluid mechanical model to describe the endothelial cell layer of the human vascular system. Such a model has to be combined with further experimental investigation using a cone-plate apparatus (Dieterich et al 2000, Buschmann et al 2004. …”
mentioning
confidence: 99%